The effect of aerobic exercise on pulse wave velocity in middle-aged and elderly people: A systematic review and meta-analysis of randomized controlled trials - Li, Gen; Lv, Yuanyuan; Su, Qing; You, Qiuping; Yu, Laikang (Frontiers in Cardiovascular Medicine, 2022)
A growing body of research examining the effect of aerobic exercise on pulse wave velocity (PWV) in middle-aged and elderly people, while findings of available studies were conflicting. The aim of this study was to explore the effect of aerobic exercise on PWV in middle-aged and elderly people. Searches were performed in PubMed, Web of Science, and EBSCO databases. Cochrane risk assessment tool was used to evaluate the methodological quality of the included literature. We included studies that satisfied the following criteria: (1) eligible studies should be randomized controlled trials (RCTs); (2) eligible studies should include both an intervention and control group; (3) eligible studies should use the middle-aged or elderly people as subjects; and (4) eligible studies should use PWV as the outcome measure. From 972 search records initially identified, 11 studies with a total of 12 exercise groups (n = 245) and 11 control groups (n = 239) were eligible for meta-analysis. There was a significant effect of aerobic exercise on reducing PWV in middle-aged and elderly people [weighted mean difference (WMD), -0.75 (95% CI, -1.21 to -0.28), p = 0.002]. Specifically, a higher intensity [vigorous-intensity, -0.74 (-1.34 to -0.14), p = 0.02; moderate-intensity, -0.68 (-1.49 to 0.12), p = 0.10], a younger age [45 ≤ age < 60, -0.57 (-0.78 to -0.37), p < 0.00001; age ≥ 60, -0.91 (-2.10 to 0.27), p = 0.13], a better health status [healthy, -1.19 (-2.06 to -0.31), p = 0.008; diseased, -0.32 (-0.64 to -0.01), p = 0.04], and a lower basal body mass index (BMI) [BMI < 25, -1.19 (-2.06 to -0.31), p = 0.008; 25 ≤ BMI < 30, -0.52 (-0.92 to -0.12), p = 0.01; BMI ≥ 30, -0.09 (-0.93 to 0.76), p = 0.84] were associated with larger reductions in PWV. Aerobic exercise, especially vigorous-intensity aerobic exercise, contributed to reducing PWV in middle-aged and elderly people. The effect of aerobic exercise on improving PWV was associated with participant’s characteristics. Specifically, a younger age, a better health status, and a lower basal BMI contributed to more significant reductions in PWV.